Influence of soil moisture on the distribution of 137Cs between the solid and liquid phases at the late stage of contamination consequences - Nikitin, Aleksander; Tagai, Svetlana; Mishchanka, Yahor; Leferd, Galina (Journal of the Belarusian State University. Ecology, 2025)
The partitioning of radioactive cesium isotopes between solids and liquid phases in soil dictates their availability for plant root uptake. This distribution is influenced by the quantity and mineral composition of the clay fraction, soil organic matter content, acidity levels, and ion concentrations in the soil solution. However, the role of soil moisture content in this partitioning remains largely unexplored. This study presents experimental findings on how soil moisture affects the mobility and bioavailability of the radionuclide 137Cs in alluvial soils. The objective was to assess how variations in soil moisture influence the concentration of 137Cs in the soil solution and its diffusion rate, which in turn impact its bioavailability. Model experiments were conducted using sod-gleyed sandy loam and sod-gley sandy alluvial soils. Analysis revealed that the minimum values of distribution coefficients of 137Cs between the solid phase and soil solution occurred at 70 % of full moisture capacity in sod-gleyed sandy loam soil and at 100% in sod-gley sandy soil. Changes in this coefficient, which directly affect the radionuclide’s bioavailability, can vary ten times or more depending on soil moisture. The study established that the diffusion rate of 137Cs in alluvial soil peaks at moisture levels between 70 and 85 % of full moisture capacity. At full saturation, the diffusion rate slightly decreases, and it declines by half when moisture is reduced to 40 %. These findings demonstrate a complex relationship between soil moisture and radionuclide mobility, which is crucial for understanding 137Cs behavior in the soil-plant system under varying conditions. The results can be utilized to enhance predictive models of cesium radionuclide behavior in the soil-plant system and to optimize radiation protection methods in agriculture.